Management training for women-what the West forgot? - Amos-Wilson, Pauline (1995)
"Drawing on experience of providing women for senior management programmes in developing countries and in the U.K., this article considers the issues associated with management training for women. In particular, it discusses the approaches currently adopted in the west, the attitudes that inform these and their shortcomings. It describes the outcomes achieved through an approach to training designed and implemented with women from developing countries, which is somewhat different to experience in the west. It goes on to suggest that at a time when developing countries are importing management training at an increasing rate from the west, measured critique should be applied to assessing the efficacy of programmes, not in respect of their appropriateness in a development context, but on a basis of whether they are effective in their place of origin. Moreover, it is argued that, in fact, the west has much to learn for its own applications from developing countries"
Keywords: Women - Training of; Management - Training of; Management education